(untitled) (ModaPalavra e-periódico, 2017)
The article discusses the affinity of wearable technologies of fashion in relation to the current technological context in which the non-human activity becomes increasingly active. The conception of the internet of things and the development of ubiquitous,pervasive and sentient communication expose a favorable view to wearable technologies. Authors such as Bruno Latour, Giselle Beiguelman and André Lemos point to a symmetrical treatment of modern dualities: physical and virtual, man and machine, nature andculture, in short, human and nonhuman. This is a current of thought that suggests the combination of dualistic poles, recognizing the hybridization process.